Photodegradation profiles of PVC compound and wood/PVC composites under UV weathering - N. Sombatsompop; K. Chaochanchaikul; V. Rosarpitak (eXPRESS Polymer Letters, 2013)
This work aimed to study the effect of different ultraviolet (UV) weathering conditions (natural and accelerated) on the photodegradation of polyvinyl chloride (PVC) and wood/polyvinyl chloride (WPVC) composites by considering the structural and physical changes of PVC and WPVC samples as well as examining the photodegradation profiles at different depths from the sample surfaces. The photodegradation of PVC and WPVC composites under natural weathering conditions were lower than those under accelerated weathering conditions. The addition of Tinuvin P stabilizer at 2 phr was sufficient to stabilize PVC and WPVC composites, whereas the presence of wood appeared to accelerate the photodegradation of PVC under both natural and accelerated weathering conditions. When considering the photodegradation profiles at different depths of the samples, it was found that the polyene and carbonyl sequences of PVC and WPVC composites were high at the sample surfaces and tended to decrease rapidly with increasing depth from the specimen surface before stabilizing at a depth of 60 μm for PVC and 80 μm for WPVC composites. The differences in specimen depths for the stabilization of polyene and carbonyl sequences in PVC and WPVC samples implied that the presence of wood particles enhanced the absorption of UV radiation by the WPVC composite samples.